Electrical, magnetoresistance and magnetotransport properties of Nd1−xSrxMnO3 - Ewe, Lay Sheng; Jemat, A.; Lim, Kean Pah; Abd Shukor, Roslan (Elsevier, 2013)
The effects of Sr substitution on the electrical, magnetoresistance and magnetotransport properties of Nd1−xSrxMnO3 were studied. Nd1−xSrxMnO3 samples were prepared using the solid-state reaction method with x=0.12, 0.152, 0.22, 0.252 and 0.32. All samples showed an orthorhombic structure, and no impurities were detected when the samples were examined using the X-ray diffraction method. The grain size was between 10 μm and 16 μm for all samples. The sample with x=0.32 showed the smallest grain size and the lowest To value, where To reflects the MnOMn bond angle. As the Sr concentration increased, the grains grew into more pentagonal and hexagonal shapes, and the insulator–metal transition temperature, Tim, also increased from 131 K to 180 K. The exceptions were the samples with x=0.152 and 0.252, where charge ordering was found at 120 K. The samples with the most pentagonal and hexagonal shaped grains (x=0.32) had the highest Tim. The magnetoresistance (MR) values were found to increase with increasing magnetic field. The sample with x=0.32 showed the highest MR value (31.5%), the highest Tim, the smallest grain size (∼10 μm) and the least bending of the MnOMn bonding angle.